Design and analysis of discrete wavelet transform (DWT) for image compression using VHDL - Al Muhit, , A; Othman, , Masuri); Islam, , MS (2005)
This paper presents the use of lectronic Design Automation (DA) for implementing the 2-D Discrete Wavelet Transform (DWT) with P G2000 standard for image compression using Aldec Active HD. tool. The design flow starts with specifications of the system behavior for implementation on silicon and it ta es several steps before hardware implementation to meet the specifications. The software allows the analysis to ensure the designed chip satisfy the re uired specifications.